SOD2 Gene Variants (rs4880 and rs5746136) and Their Association with Breast Cancer Risk - Martha P. Gallegos-Arreola; Ramiro Ramírez-Patiño; Josefina Y. Sánchez-López; Guillermo M. Zúñiga-González; Luis E. Figuera; Jorge I. Delgado-Saucedo; Belinda C. Gómez-Meda; Mónica A. Rosales-Reynoso; Ana M. Puebla-Pérez; María L. Lemus-Varela; Asbiel F. Garibaldi-Ríos; Nayely A. Marín-Domínguez; et al. (Current Issues in Molecular Biology, 2022)
The superoxide dismutase (SOD) is the principal antioxidant defense system in the body that is activated by a reactive oxygen species. Some variants of the SOD2 gene have been associated with cancer. The rs4880 variant was determined by PCR real-time and the rs5746136 variant by PCR-RFLP in healthy subjects and in breast cancer (BC) patients. The rs4880 and rs5746136 variants were associated with BC susceptibility when BC patients and the control group were compared for the CT, TT, CTCC, and the T alleles (p < 0.05). The CT genotype of the rs4880 variant showed significant statistical differences in patients and controls aged ≤ 45 years old, and with hormonal consumption (p < 0.05). The rs4880 variant was associated with BC patients with CTTT genotype and obesity, the presence of DM2-SAH, and a non-chemotherapy response (p < 0.05). Additionally, the rs5746136 variant was associated with susceptibility to BC with Ki-67 (≥20%), luminal A type BC, and a chemotherapy partial response (p < 0.05) in BC patients who carry TT, TC, and CTTT genotypes, respectively. The haplotype T/T (OR 1.98; 95% CI 1.20–3.26, p = 0.005) was observed to be a risk factor for BC. The rs4880 and rs5746136 variants in the SOD2 gene were associated with BC susceptibility.